“Neoliberalization” as Betrayal - Sharma, S. author. aut Link
XIV, 274 p. 1 illus.
Keywords: This book is concerned with the three-way relationship between neoliberalism, women's education, and the spatialization of the state, and analyses this through an ethnography lens of women's education programs in India.